TANTANGAN INTEGRASI NILAI KEBINEKAAN GLOBAL DALAM PEMBELAJARAN PKN DI SEKOLAH BERBASIS HOMOGENITAS: SEBUAH ANALISIS PROBLEMATIKA PEDAGOGIS - Nunung Mulyani; Sulton Sulton (EDUPEDIA, 2026)
This study aims to analyze the pedagogical challenges in integrating the "Global Diversity" (Kebinekaan Global) dimension of the Pancasila Student Profile into Civics Education (PKN) learning within schools characterized by homogeneous student demographics (based on religion or ethnicity). The research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews with Civics teachers, classroom observations, and curriculum document analysis at a homogenous private school. The results indicate that the primary challenge lies in the "experience gap"; students possess cognitive knowledge of diversity but lack the affective and psychomotor skills to interact with different groups due to the exclusive school environment. Teachers face difficulties in contextualizing learning materials because of the absence of direct examples of diversity in the school ecosystem. Furthermore, there is a tendency for "in-group bias" which hinders the internalization of inclusive values. The study concludes that Civics learning in homogeneous schools requires intervention through digital-based learning media and inter-school collaboration programs to present a virtual experience of diversity, ensuring that Global Diversity is not merely a theoretical concept but a lived value.